KONSEP PENDIDIKAN ISLAM MENURUT MOHAMMAD NATSIR - Mahfur Mahfur (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2009)
The research objectives of this research are: (1) What is the concept Mohammad Natsir of Islamic education?, (2) What are the cornerstone concept of thought Mohammad Natsir in Islamic education?, (3) How relevant is the idea Mohammad Natsir on the thinking of Islamic education in Indonesia today?. To answer these questions, this study used literature research. Because here is a literature review of research, the author examines the concept of thought in Mohammad Natsir with the help of books in his own writings as well as books written by others that tell about the Islamic educational thought by Mohammad Natsir. The results showed that the concept Mohammad Natsir of Islamic education that Education should be able to bring man achieve his goal, which devote themselves to God, having good character (akhlakul karimah) and got a decent living in the world. While the foundation of Islamic education is to know God, to acknowledge the ones of God and not to consider as an ally of Him. Relevance thought Mohammad Natsir to education in Indonesia today, as evidenced by the existence of public schools and Islamic school (madrasah), even schools that combine general education and religious education, as well as coordination among the schools with the holding of the National exam together.